2023
DOI: 10.2196/42549
|View full text |Cite
|
Sign up to set email alerts
|

Closed Endotracheal Suction Systems for COVID-19: Rapid Review

Abstract: Background The increase in admissions to intensive care units (ICUs) in 2020 and the morbidity and mortality associated with SARS-CoV-2 infection pose a challenge to the analysis of evidence of health interventions carried out in ICUs. One of the most common interventions in patients infected with the virus and admitted to ICUs is endotracheal aspiration. Endotracheal suctioning has also been considered one of the most contaminating interventions. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Another intervention, likely motivated by the desire to minimize the exposure of healthcare professionals to the potential risk of contamination with COVID-19 aerosols, is the reported use of closed suction systems by all respondents. It is noteworthy that in an earlier report closed suction systems failed to reduce cross-transmission in ICU patients [31]. Additionally, the American Association for Respiratory Care (AARC) 2022 guidelines state no significant differences in any outcome and recommends both systems to be safe and effective [32].…”
Section: Discussionmentioning
confidence: 98%
“…Another intervention, likely motivated by the desire to minimize the exposure of healthcare professionals to the potential risk of contamination with COVID-19 aerosols, is the reported use of closed suction systems by all respondents. It is noteworthy that in an earlier report closed suction systems failed to reduce cross-transmission in ICU patients [31]. Additionally, the American Association for Respiratory Care (AARC) 2022 guidelines state no significant differences in any outcome and recommends both systems to be safe and effective [32].…”
Section: Discussionmentioning
confidence: 98%
“…A recent review showed no difference in patient outcomes, including ventilator-associated pneumonia and mortality, between the 2 systems. 12 With closed suctioning, the ventilation circuit remains intact, preventing possible contamination from aerosols. 4 Ventilation and PEEP settings are believed to be maintained with a closed suctioning system, although this is not confirmed in a bench study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a closed suctioning system is known to reduce the amount of nursing time by 40%. 12 More research is needed to further evaluate cost-effectiveness and workload of suctioning systems.…”
Section: Discussionmentioning
confidence: 99%